Pan-metagenome reveals the abiotic stress resistome of cigar tobacco phyllosphere microbiome - Wang, Zhenhua; Peng, Deyuan; Fu, Changwu; Luo, Xianxue; Guo, Shijie; Li, Liangzhi; Yin, Huaqun (Frontiers in Plant Science, 2023)
The important role of microbial associations in mediating plant protection and responses to abiotic stresses has been widely recognized. However, there have been limited studies on the functional profile of the phyllosphere microbiota from tobacco (Nicotiana tabacum), hindering our understanding of the mechanisms underlying stress resilience in this representative and easy-to-cultivate model species from the solanaceous family. To address this knowledge gap, our study employed shotgun metagenomic sequencing for the first time to analyze the genetic catalog and identify putative plant growth promoting bacteria (PGPB) candidates that confer abiotic stress resilience throughout the growth period of cigar tobacco in the phyllosphere. We identified abundant genes from specific bacterial lineages, particularly Pseudomonas, within the cigar tobacco phyllospheric microbiome. These genes were found to confer resilience against a wide range of stressors, including osmotic and drought stress, heavy metal toxicity, temperature perturbation, organic pollutants, oxidative stress, and UV light damage. In addition, we conducted a virome mining analysis on the metagenome to explore the potential roles of viruses in driving microbial adaptation to environmental stresses. Our results identified a total of 3,320 scaffolds predicted to be viral from the cigar tobacco phyllosphere metagenome, with various phages infecting Pseudomonas, Burkholderia, Enterobacteria, Ralstonia, and related viruses. Within the virome, we also annotated genes associated with abiotic stress resilience, such as alkaline phosphatase D (phoD) for nutrient solubilization and glutamate-5-semialdehyde dehydrogenase (proA) for osmolyte synthesis. These findings shed light on the unexplored roles of viruses in facilitating and transferring abiotic stress resilience in the phyllospheric microbiome through beneficial interactions with their hosts. The findings from this study have important implications for agricultural practices, as they offer potential strategies for harnessing the capabilities of the phyllosphere microbiome to enhance stress tolerance in crop plants.